Effect of HMG extracted from urine of menopausal women on utero-ovarian weights and percentage of embryos and births of mice. - J. K. AL-Arrak (University of Baghdad, College of Veterinary Medicine, 2001)
Urine samples were collected and pooled from four menopausal women , 47-55. years old, for extraction of gonadotropines ( LH & FsH) according to the method of Albert ( 1955 ) For evaluation the hormonal extract from menopausal women the following parameter were studied: a- Effect of crude hormonal extract on utero-ovarian weights of immature mice. b- Counting number of embryos & alive births in mice treated with crude extract. There was a significant effect of hormone extracted fiom menopausal women on utero-ovaian weights for immature mice. The crude extract caused a significant increase in number of embryos and alive Lebirths compared with saline-treated mice , it is concluded that crude extract from urine of menopausal women have highly biological activity for increase fertility in female mice.